Application of Sustainable City Logistics in Saudi Arabia - Bader Alanazi; Jamal Eid Abdulaal; Herika Muhamad Taki (Politeknik Negeri Batam, 2021)
The kingdom of Saudi Arabia has advantages in trade and logistics services that other countries do not have. By 2020 there was a significant increase in logistics market revenue with reach almost SAR 94 billion (USD 25 billion), which, in this case, opens up opportunities for FDI (Foreign Direct Investment) that must be exploited. Components and logistics services are a series of activities planning, organizing, and controlling all activities in the flow of materials, from raw materials to final consumption and the return flow of manufactured products, with the aim of satisfying the needs and desires of customers and other interested parties. city. Therefore, the sustainability of city logistics requires synergy between policy makers (government) and also the community (public) with the private sector (private) with steps such as simplification of regulations, provision of urban infrastructure, low carbon emissions in transportation means of delivery of logistics services, network governance. modern traffic so that this public-private partnership is the key to the effectiveness and efficiency of a sustainable urban logistics chain.